The Patrick Star show. Season 1, volume 1 [videorecording (DVD)]. - Hillenburg, Stephen (Paramount, 2022)
Patrick Star, everyone's favorite sea star, hosts a variety show in his room inspired by the inner machinations of his mind. Patrick constantly and hilariously disrupts his family with his wild whims and surreal imagination.